(untitled) (Comprehensive Journal of Science, 2026)
This study examined the impact of psychological abuse directed at children with intellectual disabilities (Down syndrome) on mothers’ social well-being. A descriptive-analytical approach was used on a sample of 40 mothers through a questionnaire analyzed using SPSS. Results indicated that the level of psychological abuse was very low, while the social impact on mothers was moderate. A significant correlation was found between psychological abuse and certain aspects of social interaction and stigma. No statistically significant differences were found due to demographic variables.